Wild women: seekers, protagonists and goddes in sacred Indian poetry - Subramaniam, Arundhati (Gurugram Penguin Random House, 2024)
In this anthology of sacred poetry that arrives after the much-loved book, Eating God, Arundhathi Subramaniam weaves together haunting voices of, by and for women across the Indian subcontinent. Here is a lineage of audacious woman-centred spirituality that traverses the poetry of ancient Buddhist nuns, Bhakti and Sufi mystics, tantrikas and Vedantins. There are women here, and men singing as women, and both raising their voices in praise of the sacred feminine.
Keywords: Literature; English Literature; Poetry